If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(r + 7) = 5r + 69 Reorder the terms: 7(7 + r) = 5r + 69 (7 * 7 + r * 7) = 5r + 69 (49 + 7r) = 5r + 69 Reorder the terms: 49 + 7r = 69 + 5r Solving 49 + 7r = 69 + 5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5r' to each side of the equation. 49 + 7r + -5r = 69 + 5r + -5r Combine like terms: 7r + -5r = 2r 49 + 2r = 69 + 5r + -5r Combine like terms: 5r + -5r = 0 49 + 2r = 69 + 0 49 + 2r = 69 Add '-49' to each side of the equation. 49 + -49 + 2r = 69 + -49 Combine like terms: 49 + -49 = 0 0 + 2r = 69 + -49 2r = 69 + -49 Combine like terms: 69 + -49 = 20 2r = 20 Divide each side by '2'. r = 10 Simplifying r = 10
| 4x+x+3=11x-6x+3 | | 3-5x=48 | | -3x+4(5+2x)=15 | | 3q+5q=-2q+20 | | 1-4u=17 | | 39d+120=8-40 | | 4(2x+1)=12x+3-4x+1 | | -8x+9=-23 | | -4(x+3)+2x= | | 0.12x+0.3(x-1)=0.01(4x-2) | | x(x+1)(x+2)=21 | | 5x+15x-5=5(4x+6) | | 8+4n=9n-7 | | 24=7x-5-4x | | (sinx)2=0.5 | | -4+1-5m+m=m+2 | | 9(x+8)+2=38 | | 6(r-6)=-66 | | 8x(2n+3x)=10 | | 21n^2+14n+7=6n+11 | | -(4-5z)-2(-3z+4)-3z=-2(6-4z-8(1-z)) | | 5(3-5n)=65 | | 21n^2+8-4=6n+11 | | 5+6-3x=-4 | | 5a-10b=45 | | 4x+89=6x+109 | | 21n^2+8-4= | | 15-2y=15+3y | | X^2-2ax=6ab-3bx | | 5(s-1)=94-2(s-4) | | 4x-5+6=45 | | 20x=280 |